Transplantation of Rat Mesenchymal Stem Cells Overexpressing Hypoxia-Inducible Factor 2α Improves Blood Perfusion and Arteriogenesis in a Rat Hindlimb Ischemia Model - Weifeng Lu; Xiaoli Chen; Yi Si; Shichai Hong; Zhengyu Shi; Weiguo Fu (Stem Cells International)
Mesenchymal stem cells (MSCs) have been increasingly tested in cell-based therapy to treat numerous diseases. Genetic modification to improve MSC behavior may enhance posttransplantation outcome. This study aims to test the potential therapeutic benefits of rat bone marrow MSCs overexpressing hypoxia-inducible factor 2α (rMSCsHIF-2α) in a rat hindlimb ischemia model. PBS, rMSCs, or rMSCsHIF-2α were injected into rat ischemic hindlimb. Compared with the injection of PBS or rMSCs, transplantation of rMSCsHIF-2α significantly improved blood perfusion, increased the number of vessel branches in the muscle of the ischemic hindlimb, and improved the foot mobility of the ischemic hindlimb (all P<0.05). rMSCHIF-2α transplantation also markedly increased the expression of proangiogenic factors VEGF, bFGF, and SDF1 and Notch signaling proteins including DII4, NICD, Hey1, and Hes1, whereas it reduced the expression of proapoptotic factor Bax in the muscle of the ischemic hindlimb. Overexpression of HIF-2α did not affect rMSC stemness and proliferation under normoxia but significantly increased rMSC migration and tube formation in matrigel under hypoxia (all P<0.05). RMSCsHIF-2α stimulated endothelial cell invasion under hypoxia significantly (P<0.05). Genetic modification of rMSCs via overexpression of HIF-2α improves posttransplantation outcomes in a rat hindlimb ischemia model possibly by stimulating proangiogenic growth factors and cytokines.